Gamified English learning at Maahad Riyadhil Quran in Sungai Petani, Kedah / Noor Azli Affendy Lee and Muhammad Aiman Abdul Halim - Affendy Lee, Noor Azli; Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2022)
The English Language Club of UiTMCPP conducted a two- day USR programme entitled “Madrasah Visit & Exchange of Knowledge 2022” with the theme “Instilling iDART Values and Improving Wellbeing”. Subsequently, it is also a knowledge transfer programme involving the staff and student facilitators from UiTMCPP with a rural tahfiz school in Kedah, Malaysia. This programme was conducted on 14 and 15 May 2022 at Maahad Riyadhil Quran (MRIQ), Sungai Petani, Kedah.